Refugees A New Testament Perspective - Escobar, Samuel 1934- (2018)
This study builds an argument for 'embrace' as an adequate Christian response to the refugee crisis. Against the 'church as homogenous unit' missiological theory of Donald McGavran and Peter Wagner, the author argues that the list of greetings in Romans 16 proves that at least some of the house churches in Rome were mixed - migrants of different backgrounds living together. Thus Paul's exhortation to welcome one another.
Keywords: Embrace; Romans 16; Hospitality; migrant churches; refugees in the New Testament